End-of-Life Options for (Bio)degradable Polymers in the Circular Economy - Wanda Sikorska; Marta Musioł; Barbara Zawidlak-Węgrzyńska; Joanna Rydz (Advances in Polymer Technology)
End-of-life options for plastics include recycling and energy recovery (incineration). Taking into account the polymeric waste, recycling is the intentional action that is aimed at reducing the amount of waste deposited in landfills by industrial use of this waste to obtain raw materials and energy. The incineration of waste leads to recovery of the energy only. Recycling methods divide on mechanical (reuse of waste as a full-valuable raw material for further processing), chemical (feedstock recycling), and organic (composting and anaerobic digestion). The type of recycling is selected in terms of the polymeric material, origin of the waste, possible toxicity of the waste, and its flammability. The (bio)degradable polymers show the suitability for every recycling methods. But recycling method should be used in such a form that it is economically justified in a given case. Organic recycling in a circular economy is considered to be the most appropriate technology for the disposal of compostable waste. It is addressed for plastics capable for industrial composting such as cellulose films, starch blends, and polyesters. The biological treatment of organic waste leads also to a decrease of landfills and thereby reducing methane emissions from them. If we add to their biodegradability the absence of toxicity, we have a biotechnological product of great industrial interest. The paper presents the overview on end-of-life options useful for the (bio)degradable polymers. The principles of the circular economy and its today development were also discussed.